2019
DOI: 10.1097/md.0000000000017399
|View full text |Cite
|
Sign up to set email alerts
|

Yoga and schizophrenia—a comprehensive assessment of neuroplasticity

Abstract: Introduction Schizophrenia is one of the most severe mental disorders with a prevalence of about 1% and a leading cause of disability among young adults. Pharmacotherapy is the mainstay in the management of schizophrenia. However, even with the best of medication, several problems like refractoriness, negative symptoms, frequent relapses, and cognitive impairments persist. Methods This is a randomized-controlled clinical study including patients from an urban tertiary hospital and a semi-urban community cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Studies of galvanic skin response biofeedback training in schizophrenia patients have also found a statistically significant increase in BDNF serum levels after a 3-month follow-up period ( 52 ). A study protocol has been reported for measuring BDNF levels in schizophrenia patients undergoing yoga therapy, but results have not yet been published ( 53 ).…”
Section: In Patients With Chronic Schizophreniamentioning
confidence: 99%
“…Studies of galvanic skin response biofeedback training in schizophrenia patients have also found a statistically significant increase in BDNF serum levels after a 3-month follow-up period ( 52 ). A study protocol has been reported for measuring BDNF levels in schizophrenia patients undergoing yoga therapy, but results have not yet been published ( 53 ).…”
Section: In Patients With Chronic Schizophreniamentioning
confidence: 99%